The global prevalence of IBS in adults remains elusive due to the heterogeneity of studies: a Rome Foundation working team literature review. Issue 6 (27th January 2016) - Sperber, Ami D; Dumitrascu, Dan; Fukudo, Shin; Gerson, Charles; Ghoshal, Uday C; Gwee, Kok Ann; Hungin, A Pali S; Kang, Jin-Yong; Minhu, Chen; Schmulson, Max; Bolotin, Arkady; Friger, Michael; et al.
Abstract : Objectives: The global prevalence of IBS is difficult to ascertain, particularly in light of the heterogeneity of published epidemiological studies. The aim was to conduct a literature review, by experts from around the world, of community-based studies on IBS prevalence. Design: Searches were conducted using predetermined search terms and eligibility criteria, including papers in all languages. Pooled prevalence rates were calculated by combining separate population survey prevalence estimates to generate an overall combined meta-prevalence estimate. The heterogeneity of studies was assessed. Results: 1451 papers were returned and 83, including 288 103 participants in 41 countries, met inclusion criteria. The mean prevalence among individual countries ranged from 1.1% in France and Iran to 35.5% in Mexico. There was significant variance in pooled regional prevalence rates ranging from 17.5% (95% CI 16.9% to 18.2%) in Latin America, 9.6% (9.5% to 9.8%) in Asia, 7.1% (8.0% to 8.3%) in North America/Europe/Australia/New Zealand, to 5.8% (5.6% to 6.0%) in the Middle East and Africa. There was a significant degree of heterogeneity with the percentage of residual variation due to heterogeneity at 99.9%. Conclusions: The main finding is the extent of methodological variance in the studies reviewed and the degree of heterogeneity among them. Based on this, we concluded that publication of a single pooled global prevalence rate, which is easily calculated, would not be appropriate or contributory. Furthermore, we believe that future studies should focus on regional and cross-cultural differences that are more likely to shed light on pathophysiology.